The Elements Required for Multi-Stakeholder Collaboration to Achieve Sustainable Agricultural: Based on Jarwo Super Application in West Java - Ayunda, Winda Anestya; Purwaningsih, Indah (Badan Riset dan Inovasi Daerah Provinsi Jawa Timur, 2024)
The Jarwo Super innovation platform is identified as a framework for introducing Jarwo Super rice cultivation technology through the use of technological components developed for irrigated rice fields. This research examines the determining factors for the success of the collaboration process in producing agricultural innovation resulting from research and development in Indonesia. Using an innovation platform framework, this research conducted semi-structured interviews with relevant stakeholders, including researchers, policy makers, information disseminators, and local governments, to investigate multi-stakeholder perspectives. The Multi Channel Dissemination Structure (SDMC) of the Agricultural Research and Development Agency, which was created as a policy scheme starting with research, assessment, development, and application and feedback on technology, depicts actor collaboration. The findings of this study highlight the importance of three elements—demand-based participation (innovation evolution), capacity building, and commitment—for achieving multi-stakeholder collaboration. The first component, demand-based participatory, consists of implementation procedures, testing, evaluation, and research. further, the capacity building component indicates that a platform for experimentation, learning, and knowledge development is necessary for successful collaboration. The third factor is commitment which aims to encourage new developments, where the innovation platform can be a solution according to needs based on goals and vision and as a form of legitimacy for the innovation produced. We suggest that these factors can be of interest for practical application by experts to minimize uncertainty in innovation outcomes and increase the effectiveness of decision making.